2012
DOI: 10.1007/s11255-012-0253-6
|View full text |Cite
|
Sign up to set email alerts
|

Transurethral resection of ejaculatory duct in infertile men: outcome and predictors of success

Abstract: Partial EDO, whatever the etiology, has an excellent outcome after TURED. Complete EDO due to cysts appears to respond better than postinflammatory obstruction to TURED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 23 publications
1
25
0
1
Order By: Relevance
“…ducts and utricular, müllerian, and wolffian duct cysts. It has been well established in clinical practice [6][7][8], but there are very few large series of patients reported and variable surgical outcomes [9][10][11][12][13]. However, the pathogenesis of ejaculatory duct obstruction has not been well understood.…”
Section: Introductionmentioning
confidence: 99%
“…ducts and utricular, müllerian, and wolffian duct cysts. It has been well established in clinical practice [6][7][8], but there are very few large series of patients reported and variable surgical outcomes [9][10][11][12][13]. However, the pathogenesis of ejaculatory duct obstruction has not been well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors found similar outcomes, with higher patency rates with resulting improvement in sperm counts and increased number of spontaneous pregnancies for patients with m€ ullerian duct cysts after TURED compared with men with EDO secondary to other causes (10). Regardless of complete or incomplete EDO, El-Assmy et al showed improved sperm count in 72% of patients with midline cysts after TURED and improvement in only 31% of patients with noncystic causes of EDO (31). Not all researchers have as dismal an opinion about treating acquired causes of EDO.…”
Section: Transurethral Resection Of Ejaculatory Ductmentioning
confidence: 78%
“…Although 74% of all the men benefited from TURED with improved semen parameters, significantly fewer men with complete EDO had improvement compared with men with incomplete EDO (27). Similarly, El-Assmy et al found that 23.5% of men with complete EDO had improvement in their semen parameters compared with 100% men with partial EDO (31).…”
Section: Transurethral Resection Of Ejaculatory Ductmentioning
confidence: 97%
See 1 more Smart Citation
“…We hypothesize these LSV patients to have a factor affecting both semen volume and spermatogenesis that could be hormonal; we were not able to assess this possibility as only oligozoospermic patients have had reproductive hormones check-up. However, some patients may have exclusion of both sperm and seminal liquid secondary to a unilateral congenital absence of vas deferens–as observed in up-to 3% of azoospermic patients [27]–or acquired obstruction of one ejaculatory duct [28]. This indicates both systematic reproductive hormonal check-up and transrectal ultrasonography (TRUS) -independently of the value of sperm count- in further prospective studies to validate these hypotheses or not.…”
Section: Discussionmentioning
confidence: 99%